2002
DOI: 10.2118/77261-pa
|View full text |Cite
|
Sign up to set email alerts
|

Cuttings-Transport Problems and Solutions in Coiled-Tubing Drilling

Abstract: In spite of the many technological advances that have accompanied the growth of coiled-tubing (CT) drilling, one significant challenge remains-effective cuttings transport, particularly in deviated wells. This paper presents a summary of cuttings-transport problems and current solutions. It is shown that, in many circumstances, hole cleaning is more efficient if a low-viscosity fluid is pumped in turbulent flow rather than a high-viscosity fluid in laminar flow. Case studies are presented that illustrate both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Moreover, when pumping highly viscous gel sweeps during drillout operations, it has been commonly observed that the solids do not return with the sweeps but, instead, are carried within the Newtonian fluids pumped behind the sweeps. This observation is consistent with that of Leising and Walton (2002).…”
Section: Hole Cleaning and Drillout Practicessupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, when pumping highly viscous gel sweeps during drillout operations, it has been commonly observed that the solids do not return with the sweeps but, instead, are carried within the Newtonian fluids pumped behind the sweeps. This observation is consistent with that of Leising and Walton (2002).…”
Section: Hole Cleaning and Drillout Practicessupporting
confidence: 92%
“…Various unsuccessful attempts have been made to use consistent high viscous fluids for CT drillouts, but the high circulating pressure and associated pipe charge has made it uneconomical. Low viscosity Newtonian fluids, either weighted or un-weighted, are generally better suited for solids transport in the horizontal or inclined sections of the coiled tubing annulus (Leising and Walton, 2002). Without misconstruing fluids suspension capability and hydraulic solids transport, experience has shown that the use of shear-thinning high viscous sweeps with good suspension characteristics can be effective for solids removal in the inclined sections of the annulus.…”
Section: Hole Cleaning and Drillout Practicesmentioning
confidence: 99%
See 3 more Smart Citations